Crescimento e produção de amendoim submetido a ciclos de deficiência hídrica - Oliveira Júnior, José Oscar Lustosa de (1993)
A greenhouse study was conducted to evaluate water relations with the use of the porometer and pressure chamber, as well as growth and yield of two peanut cultivars submited to water stress. The treatments consisted of two water regimes (irrigated and stressed), and of two cultivars (Tatu and P1-165 317). The statistic design was the completly randomized in 2X2 factorial essay with six replications for growth and production, and two for water relations. The alterations on osmotic potential on the stressed treatment were not significant for both cultivars, proving that osmotic adjustment did not occur. Stomatal resistance increase and transpiration rate decrease proved that the peanut cultivars are very sensible to water stress. Peanut plants were able to recover rapidily from water stress by the restitution of the two parameters one day after the end of the water stress cicle. Water stress reduced both root and shoot dry matter production, and root /shoot ration. The number of secondary and tertiary ramifications was not affected by water stress. On the other hand, flower production per plant decreased substantially on both cultivars. The most productive cultivar (P1-165 317), suffered greater reductions. Plant phenology was not affected by water stress. Flowering process started at 22 day after germinated (DAG), and the peak ocurred on the second week after the beginning of the process, independent of the water regime. The peg number was less reduced by water stress then the fruits, indicating that pollination and fertilization processes was least affected by water stress then fruit filling. Drought affected both yield and harvest index of Tatu and PI-165 317 cultivars. The results permited to evaluate a better perfomance of P1-165 317 when the water availability was limited.